2001
DOI: 10.1054/bjoc.2001.1741
|View full text |Cite
|
Sign up to set email alerts
|

A weekly regimen of cisplatin, paclitaxel and topotecan with granulocyte-colony stimulating factor support for patients with extensive disease small cell lung cancer: a phase II study

Abstract: The present study was aimed at defining the antitumour activity of the cisplatin-paclitaxel-topotecan (CPT) weekly administration with G-CSF support in chemo-naive SCLC patients with extensive disease (ED-SCLC). Chemonaive ED-SCLC patients received cisplatin 40 mg/m 2 , paclitaxel 85 mg/m 2 , and topotecan 2.25 mg/m 2 weekly, with G-CSF (5 μg/kg days 3–5) support, for a maximum of 12 weeks. 37 patients were treated, for a total of 348 cycles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Frasci et al 45 reported a phase II trial of weekly IV topotecan plus cisplatin, paclitaxel and G-CSF in previously untreated SCLC with a median overall survival of 12.5 months and 1-and 2-year projected survival rates of 55% and 21% respectively. It is possible that addition of weekly topotecan to combination chemotherapy will allow for better symptom palliation and may improve response rates.…”
Section: Topoisomerase Inhibition In Sclcmentioning
confidence: 99%
“…Frasci et al 45 reported a phase II trial of weekly IV topotecan plus cisplatin, paclitaxel and G-CSF in previously untreated SCLC with a median overall survival of 12.5 months and 1-and 2-year projected survival rates of 55% and 21% respectively. It is possible that addition of weekly topotecan to combination chemotherapy will allow for better symptom palliation and may improve response rates.…”
Section: Topoisomerase Inhibition In Sclcmentioning
confidence: 99%
“…The hematologic toxicity profile of weekly topotecan is favorable compared with the 5-day regimen, and nonhematologic toxicities are generally mild and manageable. Furthermore, weekly topotecan has been successfully included in combination chemotherapy trials, including a combination regimen of topotecan, paclitaxel, and cisplatin that has shown promising safety and activity in the SCLC setting [34,37].…”
Section: Discussionmentioning
confidence: 99%
“…In the nine patients with SCLC who had not received chemotherapy before study entry, seven (78%) responded, and in patients with relapsed SCLC, four (25%) responded. Based on the MTD determined in the phase I trial, Frasci et al [37] , and G-CSF support, in previously untreated patients with extensive SCLC. Grade 4 neutropenia occurred in six (16%) patients, and grade 4 thrombocytopenia occurred in three (8%).…”
Section: Weekly Topotecan In Sclcmentioning
confidence: 99%
“…Frasci et al [37] investigated the safety and efficacy of a 12-week regimen that combined weekly treatment with cisplatin (40 mg/m ) with G-CSF support. That regimen produced a 22% CR and a 59% partial response (PR) rate in patients with extensive SCLC.…”
Section: Triplet Regimensmentioning
confidence: 99%